Off-label use of bevacizumab in patients diagnosed with age-related macular degeneration: a systematic review and meta-analysis - Estarreja, João (2024)
Background: Age-related macular degeneration (AMD) is the leading cause of vision loss in elderly people. Current pharmacological treatment in vascular AMD includes anti-VEGF agents, such as ranibizumab and aflibercept. Additionally, the off-label use of bevacizumab has been shown to be effective and has a lower cost, making it an interesting pharmacological approach; however, there is no consensus about its use. Therefore, this systematic review and meta-analysis aims to evaluate the efficacy, safety, and efficiency of bevacizumab in AMD patients. Methods: This review only focused on randomized controlled clinical trials published in 2010 in the MEDLINE database that compared the effect of bevacizumab with ranibizumab. The risk of bias in each included study was assessed using the CASP Randomised Clinical Trials checklist. Results: Twelve studies were included for qualitative synthesis, and nine of them were considered for meta-analysis. Bevacizumab-treated patients showed a significantly reduced neovascularization in a longer spectrum of time; however, they had a higher incidence of endophthalmitis than those treated with ranibizumab. Regarding efficiency, the mean number of administrations was reduced in the treatment with bevacizumab in comparison to ranibizumab. Conclusions: Clinical evidence demonstrates that bevacizumab has efficacy and safety profiles comparable with ranibizumab; however, it is relatively more efficient.